Asthma improvement in patients treated with dupilumab for severe atopic dermatitis - Dubini, Marco; Benzecry, Valentina; Rivolta, Federica; Sangalli, Andrea; Marzano, Angelo Valerio; Pravettoni, Valerio; Tavecchio, Simona; Ferrucci, Silvia Mariel (Frontiers in Allergy, 2023)
Introduction: Atopic dermatitis (AD) is considered a systemic type 2 immune driven disease, and it is associated to many atopic comorbidities including asthma. The aim of our study was to prospectively evaluate the respiratory outcomes in patients with persistent allergic asthma treated with dupilumab due to severe AD (sAD).We enrolled eligible patients with sAD for dupilumab treatment from September 2018 to December 2020. We then selected the subgroup of patients sensitized to perennial allergens. Dupilumab's efficacy and safety on AD and comorbid asthma were assessed at baseline, one month, four months, and then every 4 months up to one year.Results: A total of 437 patients with sAD were enrolled for dupilumab treatment due to sAD, and 273 reached 48 weeks of therapy. Respiratory outcomes were evaluated in the 85 asthmatic patients with positivity only to perennial allergens. Our patients showed statistically and clinically significant improvement in asthma control (Asthma Control Test and Asthma Control Questionnaire) and airway obstruction parameters (FEV1), in addition to the expected AD-related skin outcomes. Specifically, a significant improvement was achieved at the fourth month of dupilumab therapy, and this trend was maintained up to twelve months, regardless of asthma severity.Conclusions: Our results showed the overall improvement of the clinical picture that dupilumab offers for patients with severe AD and persistent allergic asthma of any severity, highlighting the importance of a global multidisciplinary approach of type 2 driven disease.Dupilumab has been approved in many countries to treat severe atopic comorbidities, including atopic dermatitis and asthma, but there are few data about its effect on asthma regardless its severity.This study prospectively evaluates the respiratory outcomes in patients with persistent allergic asthma treated with dupilumab due to severe AD up to one year, showing significant improvement in airway obstruction parameters and asthma control, regardless of asthma severity. MD, VB, and SMF contributed to conception and design of the study. AS organized the database. VP, ST and AVM contributed to analysis and interpretation of data. FR revised it critically for important intellectual content.